Bifurcation of the intratemporal facial nerve: A rare anatomical anomaly. Issue 1 (1st January 2018) - Christou, Constantina; Wikström, Johan; Strömbäck, Karin
Abstract: The anatomical position of the facial nerve is a critical factor in determining surgical candidacy in patients with congenital aural atresia (CAA). All patients with CAA must preoperatively be evaluated using a grading score based on information gained from a high resolution CT scan. In patients not suitable for surgical reconstruction, implantation of novel hearing implants is increasingly used for hearing rehabilitation. We, here, describe a bifurcation of the intratemporal part of the facial nerve in a 5-year old boy with CAA undergoing implantation with a bone conductive hearing device.